La capitale dei privilegi: Governo spagnolo, burocrazia e cittadinanza a Napoli nel Cinquecento The Capital of Privileges: Spanish Government, Bureaucracy and Citizenship in Sixteenth-Century Naples - Piero Ventura (Clio: Saggi di scienze storiche, archeologiche e storico-artistiche, 2018)
The book illustrates the reconstruction of the system of granting Neapolitan citizenship during the sixteenth century. In particular, the role played by the 'Regia Camera della Sommaria', the highest tax magistrature of the Kingdom of Naples, in the evaluation of requests and in the assignment of the citizenship licenses, which allowed access to the substantial tax and jurisdictional privileges of the capital city. The policy of the Spanish government with respect to these privileges is based on prudence and attention to the political and social balance of a fundamental and complex capital as Naples is. The 'Sommaria', however, manages in establishing a system of control and government of privileges, which makes the Neapolitan citizenship for a large part a product of the state; also subtracting expertise in the field to the city's municipal government.